Issues in neurotechnology governance - Garden, Hermann (OECD Science, Technology and Industry Working Papers, 2018)
Addressing the effects of population ageing, including the increase in mental illnesses and neurological disorders, remains a top priority for many countries and is reflected at the highest levels of international dialogue. Governments, funders, and companies around the world are making unprecedented investments in brain research and the development of neurotechnologies. Advances in brain science and neurotechnology present major opportunities for health innovation and societal benefits, but also raise difficult questions at the intersection of science, society and economy. This report provides a summary of the main discussion points emerging from the Expert Consultation on "Neurotechnology and Society", held on 14-15 September 2017, in Washington D.C., United States. Meeting participants acknowledged the increasingly international enterprise of neurotechnological innovation. Recommendations for addressing pressing ethical, legal, social, economic and cultural challenges may be beneficial to ensure responsible advancement of emerging neurotechnologies. Consideration of these issues should span laboratory, clinical, and industry settings